Phylogenetic diversity and the structure of host-epiphyte interactions across the Neotropics - Marcio R. Pie; Fernanda S. Caron; Thom Dallimore; Helena Einzmann; Peter Hietz; Michael Kessler; Flavio Nunes Ramos; João Pedro Costa Elias; Holger Kreft; Thorsten Krömer; Maria Judith Carmona Higuita; Daniel Zuleta; et al. (PeerJ, 2023)
Understanding the mechanisms driving community assembly has been a major focus of ecological research for nearly a century, yet little is known about these mechanisms in commensal communities, particularly with respect to their historical/evolutionary components. Here, we use a large-scale dataset of 4,440 vascular plant species to explore the relationship between the evolutionary distinctiveness (ED) (as measured by the ’species evolutionary history’ (SEH)) of host species and the phylogenetic diversity (PD) of their associated epiphyte species. Although there was considerable variation across hosts and their associated epiphyte species, they were largely unrelated to host SEH. Our results mostly support the idea that the determinants of epiphyte colonization success might involve host characteristics that are unrelated to host SEH (e.g., architectural differences between hosts). While determinants of PD of epiphyte assemblages are poorly known, they do not appear to be related to the evolutionary history of host species. Instead, they might be better explained by neutral processes of colonization and extinction. However, the high level of phylogenetic signal in epiphyte PD (independent of SEH) suggests it might still be influenced by yet unrecognized evolutionary determinants. This study highlights how little is still known about the phylogenetic determinants of epiphyte communities.